Strategi Komunikasi Pemasaran dalam Meningkatkan Penjualan di PT Ikan Segar Indonesia - Gunawan Dwi Dharma; Ichsan Widi Utomo; Rindana Intan Emeilia (Prisani Cendekia Institute, 2023)
The fisheries sector in Indonesia has considerable potential for development. The large potential of fisheries is also accompanied by competition and challenges for business actors in Indonesia. One of the biggest challenges faced by fisheries and marine business actors is facing the Covid-19 pandemic. The pandemic resulted in a decrease in sales of PT Ikan Segar Indonesia due to a decrease in demand from hotels and restaurants. Changes in people's purchasing behavior also have an impact on the products they buy. Through appropriate marketing communication strategies, PT Ikan Segar succeeded in increasing sales. The purpose of this research is to determine PT Ikan Segar Indonesia's communication strategy in increasing sales. The research method used in this research is descriptive qualitative with data collection techniques using observation, interviews and documentation. The research results show that PT Ikan Segar Indonesia carries out marketing communication strategies starting from the planning, implementation and evaluation stages. At the implementation stage, PT Ikan Segar implemented eight integrated marketing communication mixes starting from advertising, sales promotions, events and experiences, public relations and publicity, online marketing and social media, mobile marketing, direct and database marketing and personal sales.